A survey on pediatric emergency preparedness among health clinics in Kelantan - Abdullah, Noor Azizah (2015)
Introduction: Medical practitioner in health clinic or also known as primary care, as the first point of contact for most patients in the community need to be appropriately skilled and equipped to deal with the emergencies. Most of the previous studies showed that a substantial number of pediatric patients with potentially life-threatening emergencies presented to health clinics. However, the availability of basic emergency equipment and medication was suboptimal. As a result, patient did not receive optimal treatment that results in morbidity and mortality. In order to address the problems, numbers of guideline were published and specific training being established to the staff. Thus, this study focused on the pediatric emergency preparedness and factors influencing the preparedness. Objectives: Generally the objectives of this study were to assess paediatric emergency preparedness among health clinics in Kelantan. Specifically, to determine the characteristics of practitioners and practice those are related to preparedness for pediatric emergencies, to assess the availability of specific equipments and medications for pediatric emergencies and to study the factors that influence overall preparedness for pediatric emergencies Methods: This prospective, cross sectional study was conducted among all health clinics in Kelantan from 1st July 2015 to 31st August 2015. Only one medical officer in each health clinics was choosen to answer the questionnaire to avoid duplicate reporting of practice equipments and drugs. Results: Responses were received from 74 respondents (92.5% response rate) including information regarding the availability of equipment and medication, practitioners, and practice characteristic. 3 separate scores were calculated for each respondents; equipments score, medications score and overall preparedness score. A multiple regression analysis was used to investigate the relationship between overall preparedness score with the practitioner and practice characteristics. The mean for overall preparedness score was 87.22 of a possible 148 with standard deviation of 10.345 (n=74). In multiple linear regression analysis, only 4 factors were found to have significant association with better preparedness score. They were age, basic life support provider, availability of family physician and paramedic or ambulance response time. Conclusion: In conclusion, despite of few limitations in this study, it has shown that health clinics in Kelantan are not adequately prepared in terms of equipment and medication for pediatric emergency. There are correlation between few characteristics of practitioners and practice with the pediatric emergency preparedness among health clinics in Kelantan.